Comparison of Placental Doppler Ultrasound indices in Pregnant Women with Iron Deficiency Anemia, Minor Beta-Thalassemia and Healthy Pregnant in first half of pregnancy - Zahra Rahmani; Maryam Abdi Valikchali; Tahere Gelini Moghaddam; Shahabodin Gharahveysi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Anemia during pregnancy is a public health issue, particularly in developing countries, and is linked to adverse pregnancy outcomes such as premature birth, low birth weight (LBW), and placental growth disorders (vascular changes and placental volume). Placental growth disorder is a leading cause of perinatal and maternal mortality and a significant factor in fetal growth restriction. Given the effects of different types of anemia on pregnancy, placental vascular changes, and both long- and short-term outcomes, this study aims to examine Doppler sonographic indicators of placental spiral vessels in pregnant women with iron deficiency anemia and beta thalassemia minor and compare these with healthy pregnant women during the first half of pregnancy. Materials and methods: This case-control study was conducted on 90 pregnant women who met the inclusion criteria and attended the pregnancy care clinic at Imam Khomeini Hospital in Sari from February 23, 2019, to December 26, 2019. The participants were divided into three groups: women with iron deficiency anemia, those with minor beta-thalassemia, and healthy women (30 individuals per group). In the first half of pregnancy, participants underwent placental color Doppler ultrasound, and variables such as placental volume, pulsatility index, and resistance index of the placental spiral artery, as well as the pulsatility and resistance indices of the umbilical cord artery at the placental junction, were measured. The general linear model (GLM) was used to assess the mean differences among the three groups for these variables, and Pearson correlation was used to examine relationships between variables. Data were analyzed using SPSS statistical software version 23 (P<0.05). Results: The results indicated a statistically significant difference in the mean resistance index of the placental spiral artery among the three groups. This index was higher in pregnant women with iron deficiency anemia compared to the other two groups (2.34 in the iron deficiency anemia group, 0.7 in the beta-thalassemia minor group, and 0.99 in the healthy group; P=0.03). Additionally, the mean pulsatility index of the placental spiral artery (PIP) was significantly lower in patients with beta-thalassemia minor compared to the healthy group (1.44 vs. 2.02, P=0.02). Analysis of the correlations between different sonographic indices showed a significant positive correlation between the pulsatility index of the umbilical artery at the placental junction (PIU) and the resistance index of the umbilical artery at the placental junction (RIU) (r=0.879, P=0.001). Conclusion: The findings of this study support the value of evaluating placental indices in pregnant women, particularly highlighting the increased resistance index of the placental spiral artery in women with iron deficiency anemia. This underscores the need for follow-up by healthcare providers to prevent, assess, and treat anemia in pregnancy. Further studies are recommended to evaluate and compare vascularization of fetal and placental vessels and pregnancy outcomes in women with various types of anemia.